Potential Cost-Effectiveness of a Universal Influenza Vaccine in Older Adults. Issue 3 (14th December 2018) - France, Glenson; Wateska, Angela R; Nowalk, Mary Patricia; DePasse, Jay; Raviotta, Jonathan M; Shim, Eunha; Zimmerman, Richard K; Smith, Kenneth J
Abstract: Background and Objectives: "Universal" vaccines that could have multistrain and multiyear effectiveness are being developed. Their potential cost-effectiveness in geriatric populations is unknown. Research Design and Methods: A Markov model estimated effects of a theoretical universal influenza vaccine compared with available seasonal vaccines in hypothetical cohorts of U.S. 65+-year olds followed over a 5-year time horizon to capture potential multiyear protection. Outcomes included costs per quality-adjusted life-year gained and influenza cases avoided. Results: Using hypothetical universal vaccine parameter values (cost 100, vaccine effectiveness 39%, uptake 64%, effectiveness duration 5 years), universal vaccine was less costly than seasonal influenza vaccination strategies. High-dose trivalent influenza vaccine, compared with universal vaccine, gained 0.0028 quality-adjusted life-years and cost 82 more, or 28, 700 per quality-adjusted life-year gained. Other seasonal vaccines were not favorable economically. Five-year influenza risk with universal vaccination was 32.3% under base case assumptions, compared with <30% with adjuvanted or high-dose vaccine use. In sensitivity analyses, universal vaccine was favored when uptake or vaccine effectiveness was greater than standard-dose influenza vaccine. If absolute universal vaccine effectiveness was 10% less than standard-dose vaccine, universal vaccine could be cost-saving but not more effective than other strategies. Universal vaccine was not favored if its effectiveness duration was <3 years. Discussion and Implications: Universal vaccine use in older persons could be either cost effective or cost saving when universal vaccine parameters are within plausible ranges. However, if its effectiveness is substantially less than current vaccines, its use would probably not be favored in geriatric populations.